2023
DOI: 10.1259/dmfr.20220363
|View full text |Cite
|
Sign up to set email alerts
|

Age determination on panoramic radiographs using the Kvaal method with the aid of artificial intelligence

Abstract: Objectives: This study aimed to assess and compare age estimation on panoramic radiography using the Kvaal method and machine learning (ML). Methods and Materials: 554 panoramic radiographs were selected from a Brazilian practice. To estimate age using the Kvaal method, the following measurements were performed on the upper left central incisors and canines: tooth, pulp and root length; root and pulp width at three different levels: at the enamel–cementum junction (ECJ); midpoint between the enamel–cementum ju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…AI has primarily been used for automated age estimation by analyzing tooth development stages [ 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 ], tooth and bone parameters [ 48 , 49 , 50 ], bone age measurements [ 51 ], and pulp–tooth ratio [ 52 , 53 ]. We gathered data from the studies included, but due to the varied data samples used to assess AI model performance, a meta-analysis could not be conducted.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…AI has primarily been used for automated age estimation by analyzing tooth development stages [ 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 ], tooth and bone parameters [ 48 , 49 , 50 ], bone age measurements [ 51 ], and pulp–tooth ratio [ 52 , 53 ]. We gathered data from the studies included, but due to the varied data samples used to assess AI model performance, a meta-analysis could not be conducted.…”
Section: Resultsmentioning
confidence: 99%
“…The findings suggested a positive outcome for the semantic–radiomic association attribute. Kvaal’s method and ML yielded better results for the male dataset, with ML outperforming the Kvaal method by around 1 year across all analyzed scenarios [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Artificial intelligence (AI), a major advancement in forensic dental identification owing to the possibility of generating predictive studies and forensic automation (thereby avoiding human evaluations susceptible to subjectivity and error), has been reported to be promising in different areas of FO (Mohammad et al, 2022). In this review, four studies were identified by applying machine learning in different environments, developed by Brazilian and Colombian researchers, to simulate an identification process (Ortiz et al, 2021), distinguish between women and men using dentomaxillofacial features (Franco et al, 2022), andDAE (Becerra-Álvarez &Cortés-Osorio, 2020;Pereira de Sousa et al, 2023).…”
Section: Journal Data On Publicationsmentioning
confidence: 99%